LA CONSTRUCCIÓN SOCIAL DE SIGNIFICADOS EN EL FIN DE LA ERA DEL PADRE - Flórez-Estrada, María (Universidad de Costa Rica, 2013)
The current essay is an interpretation of the social construction of meanings from the eclosion of the Life –World in contemporary post-modernity. Also, I propose that this eclosion makes possible an epistemological leap that could further the transit from “the kingdom of necessity to the kingdom of liberty” in the dominions of culture and subjectivities. I do this mainly using Castoriadis´ vision on the social construction of imaginary meanings.